Prevalence of potentially traumatic events in Spanish university stu-dents. - Pereda, Noemí; Forns, Maria; Abad, Judit (Anales de Psicología / Annals of Psychology, 2013)
Aims: The high prevalence of traumatic events among different populations has been shown in several studies. The aim of the present study is to establish the prevalence of potentially traumatic events among Spanish university students. Methods: The sample comprised 1033 undergraduates (M = 21.71 years; SD = 2.63). Data were obtained using the Traumatic Life Events Questionnaire (TLEQ) (Kubany y Haynes, 2001). Results: Ninety-two per cent of subjects (93.4% males and 91.8% females) had been exposed to at least one potentially traumatic event. Males experienced a greater mean number of events than females (males = 3.86, SD = 2.60; females = 3.45, SD = 2.40). Sex differences were also found in the appraisal of events as being traumatic and causing major distress. Conclusions: Frequency of exposure to potentially traumatic events was higher in this sample of university students than in previous studies with similar samples. The results suggest the need for trauma screening and intervention, taking into consideration the substantial gender variation. Also the individual’s appraisal for considering an event traumatic underlines the importance of taking the individual’s perception into account.